Common name: mourning cloak (known in the United Kingdom as the Camberwell beauty) Nymphalis antiopa (Linnaeus) (Insecta: Lepidoptera: Nymphalidae: Nymphalinae) - Donald W. Hall; Jerry F. Butler (EDIS, 2009)
EENY-451, a 5-page illustrated fact sheet by Donald W. Hall and Jerry F. Butler, is part of the Featured Creatures collection. It describes this large, distinctive, and widely distributed butterfly — its distribution, description, life cycle and biology, hosts, and economic importance. Includes references. Published by the UF Department of Entomology and Nematology, June 2009. 2009 version unavailable, December 2011 and September 2014 revisions included instead.